Find the sum from the 6th term to the 12th term of the arithmetic progression 6,10,14,...?
Answers
Answered by
11
a1=6. a=10
d=10
sum from 6th to 12th can be find out by this formula
=> S12-S6
=>
![\frac{12}{2} (2 \times 6 + 11 \times 4) - \frac{6}{2} (2 \times 6 + 5 \times 4) \\ = 6(56) - 3(32) \\ = 336 - 96 \\ = 240 \frac{12}{2} (2 \times 6 + 11 \times 4) - \frac{6}{2} (2 \times 6 + 5 \times 4) \\ = 6(56) - 3(32) \\ = 336 - 96 \\ = 240](https://tex.z-dn.net/?f=+%5Cfrac%7B12%7D%7B2%7D+%282+%5Ctimes+6+%2B+11+%5Ctimes+4%29+-++%5Cfrac%7B6%7D%7B2%7D+%282+%5Ctimes+6+%2B+5+%5Ctimes+4%29+%5C%5C++%3D+6%2856%29+-+3%2832%29+%5C%5C++%3D+336+-+96+%5C%5C++%3D+240)
so your answer is 240
d=10
sum from 6th to 12th can be find out by this formula
=> S12-S6
=>
so your answer is 240
tejasr9915:
but answer is 266
Answered by
21
Similar questions
Math,
8 months ago
English,
8 months ago
Hindi,
8 months ago
Environmental Sciences,
1 year ago
Geography,
1 year ago